Éducation au patrimoine en langue minorée - Marie-Anne Châteaureynaud (Lengas)
In 1972, UNESCO created a convention for the protection and safeguarding of the world's heritage. Over time, the notion of heritage education emerged and in 2005, in Faro, UNESCO produced a framework convention that evoked a right to heritage and underlined the importance of local cultures in a globalised world.Whether tangible or intangible, the heritage linked to minority languages is thus also the subject of a cultural right from which pupils must be able to benefit.The transmission of the heritage of minority languages and cultures is a central issue because (UNESCO, 2003) "the practices, representations, expressions, knowledge and skills - as well as the instruments, objects, artefacts and cultural spaces associated with them - that communities, groups and, where appropriate, individuals" are part of cultural heritage. Thus, the theme of heritage education, a transversal and multidisciplinary theme, is envisaged as a "sharing of emotional and artistic experiences" (Musset 2012) in order to identify a community of values and to appropriate a common history, a common culture, in an intercultural dimension of otherness which allows an opening to the other.This paper aims to clarify the place of cultural heritage in the teaching of Occitan in Aquitaine in a socio-didactic framework.After having defined the notion of heritage, we will draw up an assessment of the place it currently occupies in the teaching of Occitan based on a corpus of pedagogical projects and a corpus of online resources. We will be particularly interested in the development of heritage, which is a major challenge for minority languages today. Indeed, the didactisation and networking of resources contributes to keeping alive and transmitting to students a linguistic, cultural and literary heritage. In the same way, each didactic resource can highlight the linguistic needs necessary for students' language skills (in grammar, lexicon, etc.).We will therefore develop the link between language and heritage education. Finally, we will suggest ways to educate about heritage by highlighting the value of the Occitan heritage. In this way, the pupil, placed at the centre of his or her learning, will be able to become a speaker and an actor within his or her cultural environment.